Interactive multimedia Learning science with puzzles / Cheong Ngee Sun - Cheong, Ngee Sun (2000)
Educational innovation occurs in many different ways. One approach use computer technologies to enhance the learning environment. Besides, computer assisted-learning can reduce the anxiety of students and turn out to be a positive side of learning (Gates, 1997). Children are our future leaders in the coming generation. Hence, Interactive Multimedia Learning Science with Puzzles is an interactive educational learning science with puzzles in English meant for children aged 6 to 9 years old. It comprises of an interesting storytelling with puzzles games, suitable for lower primary school (primary 1-3) for Malaysian children. It is a web based multimedia learning - teaching and can be beneficial teaching tool for parents and teachers in educating the young children because the teaching will follow closely to the KBSR Science syllabus. Interactive Multimedia Learning Science with Puzzles is developed to promote education in a more fun, easier and relaxing environment for children to learn science. Thus, it will eventually develop their interest in learning new thing. This package comprises storytelling, quiz puzzles, & puzzles games with cartoon KBSR Science syllabus. Interactive Multimedia Learning Science with Puzzles is developed to promote education in a more fun, easier and relaxing environment for children to learn science. Thus, it will eventually develop their interest in learning new thing. This package comprises storytelling, quiz puzzles, & puzzles games with cartoon animation. Software that will be used in the development of this Interactive Multimedia science with Puzzles project is Macromedia Flash 5, Adobe Photoshop and Adobe Illustrator. The approach of prototyping model is chosen for developing Interactive Multimedia Learning Science with Puzzles because it is a most widely used model & it is straightforward.